Indemnity Clause against Third Parties in Private Contracts (Comparative Study in Iran and United States’ Legal Systems) - Rouhollah Akhoundi Roshanavand; Hoda Moshfeghi (پژوهش های حقوق تطبیقی, 2025)
In the legal systems of Iran and United States, the indemnity clauses against third parties are used in order to manage risks related to the contract, and in the assumption of damage to the third party and Filing a claim for damages on his part, these clauses change the rights and duties of the parties to the contract. Since the determination of the scope, nature and effects of the indemnity clause largely depends on the agreement of the parties and the way the clause is set, the parties' understanding of the concept of this clause has a significant effect on determining the nature, effects and ultimately enforceability of this clause in judicial authorities. In this analytical and comparative research, while examining the concept of the indemnity clause against third parties, we try to deal with the nature, effects and the methods of execution of this clause in private contracts in Iran and United States’ legal systems. According to the terms of the indemnity clause, one of the parties of the contractual relationship or both of them can accept the risk of final responsibility for the loss and damages imposed on the other party due to third party claims and the indemnifier's obligation is commitment to results. Although the indemnity clauses against third parties are valid between the parties, but , in order of protect the rights of third parties, they are non-opposabillity against them.